ANALISIS PASOKAN TBS DAN HARGA CPO (STUDI KASUS KABUPATEN BENGKULU UTARA DAN PT. AGRICINAL) - Nusril, .; Arianti, Nyayu Neti; Rismaini, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
North Bengkulu Sub-Province is one of the center area palm production in Bengkulu Province. PT. Agricinal is one of the national private big plantation in North Bengkulu Sub-Province, meed needs raw material become from central plantation company and from society plantation. This Research aim to know how many FFB inclusion from society plantation North Bengkulu Sub-Province in PT. Agricinal (1), knowing result of forecast the FFB availibility in society plantation North Bengkulu Sub-Province (2) and CPO price in PT. Agricinal during 16 month future in start in 2005 September until 2006 December (3), and knowing CPO cost of goods manufactured in PT Agricinal in last period 2005 August (4). This research was carried out on 2005 September in North Bengkulu Sub-Province. The analysis data Method was adapted with that aim is descriptive analysis, exponential smoothing method and process cost of goods manufactured method. Based on result of research was knowing average FFB inclusion in PT. Agricinal from society plantation in North Bengkulu Sub-Province equal to 6.734,69 ton or 50,60% (1). Result of forecast was availibilited FFB in society plantation North Bengkulu Sub-Province for 16 period in the future had been tended increasing (2). Result of forecast of CPO price in PT. Agricinal for 16 period in the future had been tended increasing (3). And result calculation of basic CPO cost of goods manufactured in PT. Agricinal in the last period 2005 August, known that CPO cost of finish good is equal to Rp 11.637.231.132,35 and CPO cost of work in proses is equal to Rp 4.562.873,65 (4).